Implementation of graphical user interface to observe and examine the frequency and rotor angle stability of a power system due to small disturbances - Nur Ashida Salim; Mohamad Salehan Ab. Samah; Hasmaini Mohamad; Zuhaila Mat Yasin; Nur Fadilah Ab Aziz (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The aim of this research is to anticipate the stability status of a power system when the system is exposed to a change in frequency and rotor angle due to small disturbances. The proposed study was implemented on the IEEE Reliability Test System 1979 (IEEE RTS-79) which contains 24 buses, 38 transmission lines and 32 generators. Steady state stability limit of a system refers to the maximum amount of power that is permissible through the system without loss of its steady state stability. This research proposes the development of a Graphical User Interface (GUI) to observe the frequency and rotor angle stability due to the effect of small disturbances using the One Machine Infinite Bus (OMIB) technique. This proposed technique could ease the power system utility especially the power system operation to observe and examine the system frequency and rotor angle stability due to small disturbances. The findings from this research has proven that the proposed technique to observe the frequency and rotor angle stability due to small disturbances has successfully been developed using a GUI.